1998
DOI: 10.1111/j.1528-1157.1998.tb01452.x
|View full text |Cite
|
Sign up to set email alerts
|

Semiological Seizure Classification*

Abstract: Summary:We propose an epileptic seizure classification based exclusively on ictal semiology. In this semiological seizure classification (SSC), seizures are classified as follows: The SSC identifies in detail the somatotopic distribution of the ictal semiology as well as the seizure evolution. The advantages of a pure SSC, as opposed to the current classification of the International League Against Epilepsy (ILAE), which is actually a classification of electroclinical syndromes, are discussed. Key Words: Seizu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
351
1
29

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 540 publications
(395 citation statements)
references
References 5 publications
12
351
1
29
Order By: Relevance
“…Clinical evaluation included EEG monitoring and MRI. Seizures were classified according to the semiological seizure classification [17]. A developmental quotient was calculated for each case (DQ = Bayley Scales of Infant Development mental age divided by subject's biological age) as previously described [11].…”
Section: Methodsmentioning
confidence: 99%
“…Clinical evaluation included EEG monitoring and MRI. Seizures were classified according to the semiological seizure classification [17]. A developmental quotient was calculated for each case (DQ = Bayley Scales of Infant Development mental age divided by subject's biological age) as previously described [11].…”
Section: Methodsmentioning
confidence: 99%
“…In such cases, it is crucial to carefully observe which parts of the infant body are involved and how and when these body parts move, and to assess the level of consciousness of the infant (i.e., diagnosis based on the semiology of ictal events, cf. International League Against Epilepsy 2010; Lüders et al 1998). According to Nordli et al (1997), infantile seizures are often so subtle that even skilled observers may fail to identify the seizures correctly.…”
mentioning
confidence: 99%
“…Other autonomic features, such as a pale or flushed face, changes in blood pressure, or sweating, can be prominent (5,6). It has recently been suggested that such seizures be classified as autonomic, provided there is objective documentation of significant ictal autonomic changes (7). Cardiac anomalies, however, can cause syncopal events, and syncope can be associated with tachycardia, changes in facial color, sweating, and symmetric or even asymmetric convulsive movements; in such cases, these events are classified as convulsive syncope (8).…”
mentioning
confidence: 99%